Recent Trends in Humanities, Literature, Sociology and Psychology (Volume 3) - S. N. S. Gandhimathi; Sonowal, Rajlakshmi (AG Volumes, 2025)
"Recent Trends in Humanities, Literature, Sociology, and Psychology (Volume 3)" is an interdisciplinary anthology that captures the dynamic developments shaping these foundational fields of knowledge. As part of an ongoing series, this volume builds upon previous scholarly contributions by examining new directions, contemporary debates, and critical insights within the humanities and social sciences. Spanning a broad thematic spectrum, the book features essays that address pressing issues such as cultural identity, gender dynamics, mental health in the post-pandemic world, technological influences on literature and society, and the changing landscape of social relationships. It also includes critical literary explorations of classical and modern texts, with an emphasis on relevance to present-day socio-political realities. The sociological studies in this volume engage with questions of inequality, migration, education, and the structure of institutions, while the psychological analyses delve into behaviour patterns, cognitive processes, trauma, and emotional well-being. This integrated approach allows readers to draw connections across disciplines and gain a more holistic understanding of the challenges and opportunities of modern life. Intended for students, educators, researchers, and general readers with an interest in the humanities and social sciences, this volume serves as a valuable resource for keeping pace with the evolving academic and cultural landscape of the 21st century.